Effect of E’ Food Grade Preservatives and Preservation Methods on Physiochemical Characteristics, Microbial Population and Antioxidant Activity of Nipa Palm (Nypa fruticans Wurmb) Sap and Its Docking Study - Dayang Nur Athirah, Binti Abg Mohd Preudrus (University of Malaysia Sarawak Institutional Repository, 2025)
Nipa palm (Nypa fruticans) trees is one of the mangrove plants that grows wildly in coastal areas. Many products could be obtained from the tree, including nipa -sap (air nira), -syrup and -sugar (Gula Apong). Hence, it has a vast economic potential for Sarawak. However, its sap has a short shelf-life, which could contribute to low yield and bad quality of Gula Apong. This study aims to enhance the shelf-life of the sap in terms of controlling the pH, sugar content, organic acids content and its microbial growth using E’ food grade preservatives − potassium sorbate and sodium metabisulfite. Different preservation methods were tested, applying preservatives before (pre-tapping) and after sap collection (post-tapping), and in solid (effervescent granules) or liquid (aqueous neutralizing solution) forms. The study was conducted at two locations: Kampung Pinggan Jaya (Site I, using plastic bottle) and Pusa (Site II, using bamboo vessel). Samples treated with effervescent granules (Sample X, Y, M and N) were collected at both sites, while samples treated with neutralizing aqueous solution (Sample A and B) were collected at Site I. The preservation methods tested were introducing the preservative during pre-tapping (Sample X, M and A); the preservative was added into the empty bottle before the tapping begins and post-tapping (Sample Y, N and B); the preservative was added after the sap has been collected. Changes in physical appearance has been evaluated using sensory evaluation method, meanwhile pH and sucrose content were measured on-site at every one-hour interval. Due to the remote location of Site II, further analysis could not be conducted. Only on-site experiments, such as pH, sensory evaluation, and sucrose content, were performed at Site II. The results showed that pre-tapping treatments preserved more sucrose (Sample X: 112.0 ± 0.4 g/L, Sample M: 110.0 ± 0.5 g/L, Sample A: 150.0 ± 0.1 g/L) than post-tapping treatments (Sample Y: 116.0 ± 0.4 g/L, Sample N: 105.0 ± 0.3 g/L, Sample B: 145.0 ± 0.4 g/L) after 24 hours of storage. Further analysis showed that treated samples (both pre- and post-tapping) exhibited lower glucose and fructose concentrations compared to their controls. Sample A showed the lowest reducing sugar concentration (51.8 ± 2.4 g/L), followed by Sample B (51.3 ± 2.0 g/L), Sample X (67.6 ± 2.8 g/L) and Sample Y (63.6 ± 2.5 g/L). Sample A (0.95 g/L) and Sample B (0.97 g/L) had lower concentration of lactic acid compared to Sample X (1.15 g/L) and Sample Y (1.08 g/L). Sample A (0.08 g/L) and Sample B (0.07 g/L) also had lower acetic acid levels compared to Sample X (0.12 g/L) and Sample Y (0.09 g/L). The control sample experienced a rapid decline in RSA, dropping from 32.39 ± 0.31% at 8 hours to just 9.33 ± 0.36% at 24 hours. Pre-tapping samples (X and A) maintained higher antioxidant activity, with Sample X showing 37.32 ± 1.27% at 8 hours and 29.39 ± 2.57% at 24 hours, and Sample A showing 48.91 ± 0.99% at 8 hours and 45.38 ± 1.30% at 24 hours. In contrast, post-tapping samples (Y and B) showed lower antioxidant retention, with Sample Y at 32.55 ± 7.93% at 8 hours and 22.52 ± 6.34% at 24 hours, and Sample B at 39.95 ± 1.07% at 8 hours and 30.46 ± 0.81% at 24 hours. The study on antimicrobial activity showed that the pre-tapping treatments were more effective at reducing bacterial counts than post-tapping treatments. Sample A had the lowest bacterial counts, ranging from 1.47×103 CFU/mL at 10⁻¹ to TFTC at 10⁻⁶, showing the highest antimicrobial activity. This antimicrobial effect was comparable to the activity of VCO or its active compound, lauric acid, which was used as a reference for evaluating antimicrobial efficacy in the treated sap. Overall, the results suggested that the aqueous preservative reacts faster as it is already dissolved, which leads to a faster reaction rate compared to effervescent granules preservatives. Docking simulations showed that potassium sorbate binding strongly with glucose oxidase through hydrophobic interactions, with the most stable conformation showing a binding affinity of -4.9 kcal/mol.